The Effects of Bazedoxifene, Conjugated Equine Estrogens, and a Tissue Selective Estrogen Complex (TSEC) Containing Both Bazedoxifene and Conjugated Equine Estrogens on Cerebral Artery Atherosclerosis of Postmenopausal Monkeys - Clarkson, Thomas B. (2014)
OBJECTIVE: To evaluate the effects of a new selective estrogen receptor modulator (bazedoxifene acetate, BZA) and a tissue specific estrogen complex (TSEC = BZA combined with conjugated equine estrogens (CEE), on atherosclerosis extent and severity of cerebral arteries. METHODS: Ninety-eight surgically postmenopausal monkeys (Macaca fascicularis) were fed a moderately atherogenic diet and then randomized to receive no treatment, or women’s equivalent doses of BZA (20 mg/day), CEE (0.45 mg/day) or BZA+CEE. After an experimental period of 20 months (approximately equivalent to 5 years of patient experience), the extent and severity of atherosclerosis in the common carotid artery, carotid bifurcation, internal carotid artery and the basilar artery was determined. Lesion severity was determined using the American Heart Association grading system (AHA, grades 0-5). RESULTS: BZA had no consistent adverse effects on the extent or severity of atherosclerosis in the cerebral arteries and did not attenuate the beneficial effects of CEE on common carotid artery atherosclerosis severity. Although CEE had only modest beneficial effects on atherosclerosis extent of the carotid bifurcation, the severity of lesions and numbers of affected cases in the common carotid artery were reduced with CEE treatment. As reported previously, plasma lipid profiles did not differ among the treatment groups. CONCLUSIONS: In this long-term (equivalent to 5 human patient years) nonhuman primate trial, BZA had no consistent adverse effect on cerebral artery atherosclerosis and did not attenuate the modest beneficial effect of CEE on common carotid arteries. Furthermore, CEE inhibited the development of complicated plaques in the common carotid artery